Pengaruh Harga dan Promosi terhadap Loyalitas Pelanggan Kopi Starling di Kota Depok: The Effect of Price and Promotions on Customer Loyalty at Kopi Starling in Depok - Muhammad Roni Setiawan; Susan Rachmawati (CV Warnak Johanna Nusantara, 2026)
The development of the coffee industry in Indonesia has led to the emergence of various business models, one of which is mobile coffee (Starling), which is growing rapidly in Depok City. Increasingly fierce competition requires mobile coffee businesses to implement appropriate marketing strategies, particularly in terms of price and promotion, in order to build customer loyalty. However, the role of price and promotion in shaping the loyalty of mobile coffee customers is still unclear. This study aims to analyze the effect of price and promotion on the loyalty of Starling Coffee customers in Depok City, both partially and simultaneously. This study uses a quantitative method with a descriptive and associative approach. Data were collected through a questionnaire distributed to 97 respondents who had made at least two purchases. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that, partially, price had a positive and significant effect on customer loyalty with a significance value of 0.000 (<0.05), and promotion also had a positive and significant effect with a significance value of 0.003 (<0.05). Simultaneously, price and promotion have a significant effect on customer loyalty with an F-test significance value of 0.000 and a coefficient of determination (R²) of 0.45.